Properties of a purified pore-forming protein (perforin 1) isolated from H-2-restricted cytotoxic T cell granules (The Rockefeller University Press, 1986)
Histocompatibility-restricted cytotoxic T lymphocytes produce circular lesions on target cell membranes. The pore-forming protein (PFP or perforin 1) that forms these membrane lesions has been purified from lymphocytes. At 37 degrees C, in the presence of Ca2+, this protein polymerizes into a supramolecular tubular complex of Mr greater than 10(6) that partially resists dissociation by SDS and reducing agents. It incorporates spontaneously into planar lipid bilayers during polymerization to form nonselective ion channels, showing heterogeneous size distribution, the smallest conductance per unit being identified as 400 pS in 0.1 M NaCl. PFP/P1 that had been assembled in lipid vesicles before incorporation into planar bilayer show much larger single channel conductance, ranging from 1 to 6 nS in 0.1 M NaCl, suggesting that PFP/P1 may assume multiple functional sizes in proportion to its state of polymerization. The reconstituted channels are relatively voltage-insensitive, with most channels persisting in the open state for seconds to minutes. Nucleated cells are rapidly depolarized by this protein. The purified protein lyses a variety of tumor cells. Polymerization and functional channel activity are absolutely Ca2+-dependent. The activity of this protein may play a direct role in T lymphocyte-mediated cytolysis.